Immigration Policy : Methods of Economic Assessment - Don J. DeVoretz (Institute for the Study of Labor (IZA), 2004)
This paper outlines a set of economic criteria to assess an immigrant receiving country?s immigration policy from three perspectives. These three perspectives include the resident population, the immigrant and the sending country viewpoints. An expanded version of Julian Simon?s financial transfer model which includes employment and capital externalities is developed to assess the efficacy of an immigration policy from the resident?s viewpoint. Next, Chiswick?s earnings ?catch-up? model is expanded in an employment dimension to create an assessment criterion for the resident immigrant population. Finally, a comprehensive reverse transfer criterion is outlined to provide an assessment criterion for sending regions. These criteria are then applied to European and North America immigrant receiving countries.
Keywords: J68; 330; immigration workers; public policy; Migrationspolitik; Einwanderungsrecht; Kosten-Nutzen-Analyse; Westeuropa; Nordamerika